Facile Synthetic Protocols for the Preparation of New Impurities in Pemetrexed Disodium Heptahydrate as an Anti-cancer Drug - Jaggavarapu, Rama M. R.; Muvvala, Venkatanarayana; Ghojala, Venkatareddy; Babu, H. S.; Cheedarala, Ravi Kumar (Current Organic Synthesis, 2022)
A facile synthetic protocol was employed to prepare process-related impurities associated with the synthesis of pemetrexed disodium heptahydrate, Alimta. The research work is described for the development of the novel synthetic methods and their structure elucidation of Pemetrexed glutamide, N-methyl pemetrexed, and N-methyl pemetrexed glutamide impurities. The listed impurities were deduced through spectral analysis, such as 1H-NMR, 13CNMR, and HRMS. The target compounds can be used as the reference substances for quality control.
Keywords: alimta